Application of LSB Steganography for Encrypted Data Using Triple Transposition Vigenere on Digital Images - Eko Aribowo; Windy Sayyida Amalya; Nur Rochmah Dyah Puji Astuti (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2025)
Data security threats emerge when sensitive information is transmitted without sufficient protection, exposing it to unauthorized access. Steganography, particularly the Least Significant Bit (LSB) technique, is widely adopted due to its simplicity and minimal impact on digital image quality. Nevertheless, it is prone to detection through steganalysis attacks. This research improves the LSB method by incorporating Vigenere and Triple Transposition algorithms. The Vigenere algorithm secures text by shifting characters based on a key, mitigating the limitations of single permutations, but it remains vulnerable to frequency analysis if the key is too short. Triple Transposition enhances security by applying three rounds of encryption with distinct keys, making decryption significantly harder. This study utilizes grayscale and RGB images from the USC SIPI database. Grayscale images offer advantages in terms of storage and algorithm efficiency, while RGB images provide broader color diversity and versatile applications. By combining these methods, the proposed approach strengthens data security, ensuring embedded messages are more resilient against advanced steganalysis and unauthorized decryption attempts. The integration aims to improve the robustness of LSB steganography, addressing its limitations while effectively securing sensitive information